Review of Invertebrate Biological Control Agents Introduced into Europe - Schaffner, Urs
This review provides an overview of all documented releases of exotic (non-European) invertebrate biological control agents (IBCAs) into the environment in Europe and summarizes key information on the target species as well as on the biological control agent released. It is an update of A Review of Biological Control in Western and Southern Europe edited by Greathead (1976) and covers the period from 1897, when the beetle Rodolia cardinalis was introduced into Portugal against the invasive cottony cushion scale, Icerya purchasi, until the end of 2009. This review is based largely on the BIOCAT database (Greathead and Greathead 1992), which contains records of the introduction of insect natural enemies, namely parasitoids and predators, for the control of insect pests worldwide. This review may not provide the complete list of BC agents introduced into Europe. Nevertheless, the report includes a vast majority of the introductions, and hence provides a representative picture of the history of releases of exotic BC agents into the environment in Europe.